Estudio de pre factibilidad económica del manejo de residuos industriales de la empresa Jepri Recicladora (2017)
As part of a productive chain and reverse logistics, every industry has the need to make good waste management, a process that is carried out by third parties such as Jepri Recicladora, who is a company with more than 15 years in the market. of integral management of industrial waste, especially pharmaceutical waste. The company in need of growth as a management objective will carry out a study of all the internal and external aspects to find the possibility of entering to participate in international markets indicating in Latin America.